Introduction to Diesel Emissions - Viskup, Richard; Viskup, Richard (IntechOpen, 2020)
The first invention and development of the functional diesel engine was in 1897 by Rudolf Christian Karl Diesel, German inventor. Until now, this invention has been superseded by the development of very productive engines and mechanics. Current diesel engines are well known to many people around the world and serve in innumerable applications for various types of public transport, light and heavy duty transportation, for automotive, railway, maritime or aviation transportation, in different harsh environments, in construction, in mining, and for diverse industries. The light duty or heavy-duty diesel engines have some drawbacks. One of the main concerns is connected with exhaust emissions generated by diesel engines. This book discusses the generation of diesel exhaust emissions and mitigations, performance, emissions and combustion evaluations, utilisation of alternative biodiesel fuels, comparison of different techniques for measurement of soot and diesel particulate matter, analyses of diesel particulate matter flow pattern, and chemical composition of diesel particulate matter. The main concern of this book is to expand knowledge of readers and bring together the latest research findings related to diesel engine exhaust emissions.
Keywords: Petroleum technology